HIV and measures to control infection in general practice. Issue 6731 (21st April 1990) - Foy, C; Gallagher, M; Rhodes, T; Setters, J; Philips, P; Donaldson, C; Bond, J; Moore, M; Naji, S
Abstract : OBJECTIVE–To assess the impact of HIV on procedures to control infection in general practices. DESIGN–A postal questionnaire survey. SETTING–General practices throughout Britain. SUBJECTS–5359 General practitioners, 3429 (63.9%) of whom returned the questionnaire. MAIN OUTCOME MEASURE–Response to questionnaire on knowledge about HIV and policies for controlling infection. RESULTS–Most doctors (2018) had started to wear gloves when taking blood. Almost half (1510) had not resheathed needles previously but a further 776 had adopted this policy because of HIV. Over half of the doctors did not know or were unsure about the risk of infection from needlestick injuries, and 1759 had no practice policy for controlling infection. CONCLUSIONS–Many doctors are uncertain about measures to control infection in general practice. More information and advice are needed to help doctors develop policies to protect patients and staff.